2023
DOI: 10.1093/jee/toad189
|View full text |Cite
|
Sign up to set email alerts
|

Rapid assay using recombinase polymerase amplification and lateral flow dipstick for identifying Agrilus mali (Coleoptera: Buprestidae), a serious wood-boring beetle of the western Tianshan Mountains in China

Cheng-Jin Li,
Hui-Quan Sun,
Wen-Xia Zhao
et al.

Abstract: Agrilus mali stands as a significant wood-boring pest prevalent in Northeast Asia. Identifying this pest beetle is often hindered by insufficient efficient, rapid, on-site discrimination methods beyond examining adult morphological features. As a result, an urgent need arises for developing and implementing a rapid and accurate molecular technique to distinguish and manage the beetle. This study presents a straightforward, swift, highly specific, and sensitive method built upon recombinase polymerase amplifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In contrast, the SS-PCR method offers a cost-effective solution while maintaining high performance. Furthermore, it is relatively resistant to aerosol contamination, addressing a common issue observed in many isothermal amplification techniques [ 53 ]. In another study, we found that the selection of target genes in higher-resolution detection technologies may be related to their evolutionary, as these technologies are more sensitive to detecting individual base pair matching sites, such as RPA [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the SS-PCR method offers a cost-effective solution while maintaining high performance. Furthermore, it is relatively resistant to aerosol contamination, addressing a common issue observed in many isothermal amplification techniques [ 53 ]. In another study, we found that the selection of target genes in higher-resolution detection technologies may be related to their evolutionary, as these technologies are more sensitive to detecting individual base pair matching sites, such as RPA [ 53 ].…”
Section: Discussionmentioning
confidence: 99%